2014
DOI: 10.1097/acm.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Modernizing and Transforming Medical Education at the Kilimanjaro Christian Medical University College

Abstract: The Kilimanjaro Christian Medical University (KCMU) College and the Medical Education Partnership Initiative (MEPI) are addressing the crisis in Tanzanian health care manpower by modernizing the college’s medical education with new tools and techniques. With a $10 million MEPI grant and the participation of its partner, Duke University, KCMU is harnessing the power of information technology (IT) to upgrade tools for students and faculty. Initiatives in eLearning have included bringing fiber-optic connectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…MEPI has helped to support medical education through collaborative relationships and e-learning initiatives throughout Sub-Saharan Africa [7,12]. The experience and perceptions of e-learning initiatives may vary between institutions in Africa, and the experience at AAU has likely been impacted by the rapidity and degree of the scale up of medical student class size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MEPI has helped to support medical education through collaborative relationships and e-learning initiatives throughout Sub-Saharan Africa [7,12]. The experience and perceptions of e-learning initiatives may vary between institutions in Africa, and the experience at AAU has likely been impacted by the rapidity and degree of the scale up of medical student class size.…”
Section: Discussionmentioning
confidence: 99%
“…The funding was also used to install a learning management system (LCMS+) that had been previously used and optimized for over a decade at Duke University School of Medicine. An evaluation of these initiatives found that 90% of first year medical students at KCMUC accessed the online curriculum frequently one year after its implementation [12]. While there had been an increase in the number of medical student at KCMUC (from 15 to 155 per class) it took place over more than a decade, while at AAU the increase of more than 250 students per class (from <100 up to 350) took place within only a few years.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies, we found that computer knowledge and utilization among community health workers in Sub-Saharan Africa is low [ 15 , 24 , 26 ]. Similarly, we found that the lack of infrastructure for ICT impedes the implementation of eLearning initiatives [ 29 , 30 ]. Due to resource limitations and infrastructural challenges within villages, HSAs were provided with smartphones rather than laptop computers.…”
Section: Discussionmentioning
confidence: 99%
“…Also, they should allow low-income countries to adopt a “diagonal” approach to development and strengthen institutions and systems [ 13 , 26 – 28 ]. For example, many sub-Saharan African countries participating in MEPI, as well as Rwanda (as the host-country for the HRH Program), have utilized funds for infrastructure and equipment within health professional schools and teaching hospitals [ 15 , 25 , 29 ]. Moreover, all academic institutions participating in the HRH Program have agreed to charge overhead costs at less than 10% [ 15 ], while Seed Global Health (as partner non-governmental organization [NGO]) charges no overhead costs for its implementation of GHSP.…”
Section: New Models For Increasing Health Workforce Capacitymentioning
confidence: 99%